2011
DOI: 10.1111/j.1365-2958.2011.07928.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural effects of seven‐residue deletions on the coiled‐coil cytoplasmic domain of a chemoreceptor

Abstract: SummaryChemoreceptors transmit signals from the environment to the flagellar motors via a histidine kinase that controls the phosphorylation level of the effector protein CheY. The cytoplasmic domain of chemoreceptors is strongly conserved and consists of a long alpha-helical hairpin that forms, in the dimer, a coiledcoil four-helix bundle. Changes in this domain during evolution are characterized by the presence of sevenresidue insertions/deletions located symmetrically with respect to the hairpin turn, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…We have previously demonstrated that Tar forms mixed trimers of dimers with two different 34H-class receptors from Rhodobacter sphaeroides, McpB and McpH, as well as with a Tsr-derived construct in which the deletion of a heptad in each arm of its cytoplasmic domain converts it into a 34H-like MCP (Massazza et al, 2012). In those experiments, mixed trimer formation was accompanied by a significant impairment of Tar-mediated signalling, suggesting that a structural distortion in the trimers interferes with function.…”
Section: Discussion Pctapp Signalling Abilities Within E Coli Complexesmentioning
confidence: 99%
“…We have previously demonstrated that Tar forms mixed trimers of dimers with two different 34H-class receptors from Rhodobacter sphaeroides, McpB and McpH, as well as with a Tsr-derived construct in which the deletion of a heptad in each arm of its cytoplasmic domain converts it into a 34H-like MCP (Massazza et al, 2012). In those experiments, mixed trimer formation was accompanied by a significant impairment of Tar-mediated signalling, suggesting that a structural distortion in the trimers interferes with function.…”
Section: Discussion Pctapp Signalling Abilities Within E Coli Complexesmentioning
confidence: 99%
“…Variants carrying point mutations that suppressed the chemotaxis defects exhibited by the TsrH18 original construct were isolated as described in Massazza et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…Candidate mutants were verified by sequencing the entire protein-coding region. Variants carrying point mutations that suppressed the chemotaxis defects exhibited by the TsrH18 original construct were isolated as described in Massazza et al (2012).…”
Section: Construction Of the 40h-class Tsr Derivativesmentioning
confidence: 99%